1985
DOI: 10.1002/chin.198552311
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS AND BIOLOGICAL ACTIVITY OF 3′‐AZIDO‐ AND 3′‐AMINO SUBSTITUTED NUCLEOSIDE ANALOGS

Abstract: Die Verbindungen (I) reagieren nach A) unter Bildung der Azide (III) und (IV) sowie der Anhydrouracile (V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The only modification in structure 11 is that the R,βunsaturated ketone in M02 has been replaced by a bioisosteric amide, which was based on the same considerations with regard to toxicity as described above. To clarify the role of the 3,5diphenyl-1H-pyrazole moiety of M02 in its antiviral activity, 3,5-diphenyl-1H-pyrazole (17) itself was tested for antiviral activity.…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The only modification in structure 11 is that the R,βunsaturated ketone in M02 has been replaced by a bioisosteric amide, which was based on the same considerations with regard to toxicity as described above. To clarify the role of the 3,5diphenyl-1H-pyrazole moiety of M02 in its antiviral activity, 3,5-diphenyl-1H-pyrazole (17) itself was tested for antiviral activity.…”
Section: Designmentioning
confidence: 99%
“…Cryo-electron microscopy and X-ray crystallography studies of various flavivirus E protein fragments have revealed that domains I and II are connected by a mobile hinge that allows rotation of DII relative to DI-DIII during the processes of viral maturation and fusion of the viral envelope with the host cell membrane 1417. Mutations that affect the pH threshold for either fusion or virulence are clustered in this hinge region 1823.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation